Asymmetric effects and long memory in the volatility of Dow Jones stocks - Marcel Scharth; Marcelo C. Medeiros (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
Does volatility reflect a continuous reaction to past shocks or changes in the markets induce shifts in the volatility dynamics? In this paper, we provide empirical evidence that cumulated price variations convey meaningful information about multiple regimes in the realized volatility of stocks, where large falls (rises) in prices are linked to persistent regimes of high (low) variance in stock returns. Incorporating past cumulated daily returns as a explanatory variable in a flexible and systematic nonlinear framework, we estimate that falls of different magnitudes over less than two months are associated with volatility levels 20% and 60% higher than the average of periods with stable or rising prices. We show that this effect accounts for large empirical values of long memory parameter estimates. Finally, we analyze that the proposed model significantly improves out of sample performance in relation to standard methods. This result is more pronounced in periods of high volatility.
Keywords: 330; Realized volatility; long memory; nonlinear models; asymmetric effects; regime switching; regression trees; smooth transition; value-at-risk; forecasting; empirical finance.; Börsenkurs; Aktienindex; Volatilität; Schätzung